Windows 11 - Simpson, Alan, 1953- (--For dummies., 2024)
'Windows 11' brings you up to speed on the latest version of Windows, so you can make your PC operate the way you need it to with no guesswork. This straightforward and approachable resource helps you keep your PC or laptop humming, helping you do things like create user profiles, get connected to networks, find lost files, make your computer play nice with a printer, and fix the most common Windows hiccups.